Control Strategies for Electronically Controlled Limited Slip Differentials - Carlén, Mattias; Yngve, Simon (My University, 2006)
The objectives of this master thesis work were to develop control strategies for electronically controlled limited slip differentials with main aspect on the yaw rate. The control strategies were developed in Matlab/Simulink with the use of VehSim, GM version of the commercial product CarSim. An ideal electronically controlled LSD (eLSD) and a new invention called Direction Sensitive Locking Differential (DSLD) were evaluated. A bicycle model was derived to use as a reference model and an extended model was derived to show the influence on the vehicle behaviour from the differential. The control strategy implemented for the eLSD combines logic with a variable PID-controller and the strategy for the DSLD was based on logic. To evaluate the control strategies, four different driving scenarios were simulated. The results from the simulations are that with the control strategies developed in this master thesis work the vehicle’s stability, traction and cornering performance are enhanced significantly.
Keywords: Teknisk mekanik; Farkostteknik; Applied Mechanics; Vehicle Engineering